Housing market bubbles and business cycles in an agent-based credit economy - Einar Jon Erlingsson; Andrea Teglio; Silvano Cincotti; Hlynur Stefansson; Jon Thor Sturlusson; Marco Raberto (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
This paper investigates the housing and mortgage markets by means of an agent-based macroeconomic model of a credit network economy. A set of computational experiments have been carried out in order to explore the effects of different households' creditworthiness conditions required by banks in order to grant a mortgage. Results show that easier access to credit inflates housing prices, triggering a short run output expansion. However, the artificial economy becomes more unstable and prone to recessions. With stricter conditions the economy is more stable and does not fall into serious recessions, although a too severe regulation can slow down economic growth.
Keywords: G21; E20; E25; R31; R38; 330; Credit cycles; housing market; agent-based model; subprime lending